In vitro inhibitory effects of Liangxue-Wuhua decoction on pathogenic bacteria associated with acne vulgaris - Xinyi FENG; Jianqing FENG; Zhongsheng MIN; Lihua ZHUANG; Wenxiang MA (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To study the inhibitory effects of Liangxue-Wuhua decoction at different concentrations on acne vulgaris-related pathogens (Propionibacterium acnes, Staphylococcus epidermidis, Staphylococcus aureus) in vitro. Methods Conventional plate method was used to culture propionibacterium acne, Staphylococcus epidermidis and Staphylococcus aureus. The antibacterial assay and zone of inhibition were used to assess the inhibitory effects of Liangxue-Wuhua decoction at different concentrations. Erythromycin was used as positive control. The minimum antibacterial concentration (MIC) and minimum bactericidal concentration (MBC) were determined. Results The MICs of Liangxue-Wuhua decoction for Propionibacterium acne, Staphylococcus epidermidis and Staphylococcus aureus were 125 mg/mL, 125 mg/mL and 500 mg/mL, respectively, and BMCs were 250 mg/mL, 250 mg/mL and 1 000 mg/mL, respectively. The MICs of erythromycin for Propionibacterium acne, Staphylococcus epidermidis and Staphylococcus aureus were 0.1 mg/mL, 6.25 μg/mL and 0.05 mg/mL, respectively, and BMCs were 0.2 mg/mL, 6.25 μg/mL and 0.1 mg/mL, respectively. Conclusion Liangxue-Wuhua decoction does-dependently inhibits Propionibacterium acne, Staphylococcus epidermidis and Staphylococcus aureus in vitro.